Dakota : a novel - Grimes, Martha (New York : Viking, 2008)
Young Andi Oliver is an amnesiac and drifter who awoke in a Santa Fe bed and breakfast with a man's belongings tossed about the room. Adopting a name from the initials on her backpack, Andi moves from one waitress job to the next, from Idaho to North Dakota, until she takes a job at Klavan's, a massive pigfarming facility that specializes in the dark art of modern livestock management. As Andi begins to uncover the truth about Klavan's and a slaughterhouse called Big Sun, two men are on her trail, one a gunman hired to kill her, another who has followed her across three states demanding something from her forgotten past.--From publisher description
Keywords: Drifters -- Fiction; Amnesiacs -- Fiction